2017
DOI: 10.1021/acs.iecr.7b01351
|View full text |Cite
|
Sign up to set email alerts
|

Can Fibrous Mats Outperform Current Ultrafiltration and Microfiltration Membranes?

Abstract: Ultrafiltration (UF) and microfiltration (MF) membranes have important applications in separations related to proteins, pharmaceutical products, viruses, food and beverages, water treatment, and sterilization. Although phase inversion membranes have been used for MF and UF applications for decades, there has been, instead, an increase in interest in using electrospun fibrous mats as MF/UF membranes. Although the selectivity–permeability tradeoff for conventional phase-inversion UF membranes is now established,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Electrospinning can be used to manufacture textiles on the commercial scale that are comprised of randomly accumulated nanofibers with large surface-to-volume ratios, high specific surface areas, large interstitial spaces, and porosity values greater than 80%. , Nanofibers show promise in a wide range of separation applications, including membrane distillation, adsorption, pretreatment of feed, and reverse osmosis membranes. Models have suggested that the performance of freestanding nanofiber mats with small fiber diameters of ∼2 and ∼70 nm with membrane thicknesses of <100 and <1000 nm, respectively, would surpass that of current ultrafiltration and microfiltration membranes . When Liu et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Electrospinning can be used to manufacture textiles on the commercial scale that are comprised of randomly accumulated nanofibers with large surface-to-volume ratios, high specific surface areas, large interstitial spaces, and porosity values greater than 80%. , Nanofibers show promise in a wide range of separation applications, including membrane distillation, adsorption, pretreatment of feed, and reverse osmosis membranes. Models have suggested that the performance of freestanding nanofiber mats with small fiber diameters of ∼2 and ∼70 nm with membrane thicknesses of <100 and <1000 nm, respectively, would surpass that of current ultrafiltration and microfiltration membranes . When Liu et al .…”
Section: Introductionmentioning
confidence: 99%
“…24−27 Models have suggested that the performance of freestanding nanofiber mats with small fiber diameters of ∼2 and ∼70 nm with membrane thicknesses of <100 and <1000 nm, respectively, would surpass that of current ultrafiltration and microfiltration membranes. 28 When Liu et al 19 deposited a ∼5 μm-thick layer of carbon nanofibers (diameter: 20−40 nm) onto ultrafiltration membranes, they demonstrated a minimal pure water flux decline and an improved removal of natural organic matter, including sodium alginate and bovine serum albumin. A layer of poly(acrylic acid) and poly(vinyl alcohol) nanofibers (<2 mg/cm 2 ) was electrospun onto ultrafiltration membranes, causing an increase in membrane hydrophilicity and a reduction in organic fouling without affecting permeability or protein rejection performance.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Nanofibrous membranes, which are composed of electrospun nanofibers with random orientation, have several unique characteristics such as a large surface area to unit volume ratio, high porosity (up to >80%), nanosize pores and fully interconnected pores [ 23 , 24 , 25 ]. With these properties, nanofibrous membranes provide abundant water pathways with low hydraulic resistance and have drawn remarkable attention in microfiltration with high water flux and low-energy consumption [ 26 , 27 ]. Recently, polyacrylonitrile (PAN) nanofibrous membrane was applied as nanofibrous scaffold for a high flux thin-film nanofibrous composite (TFNC) nanofiltration membrane and it exhibited over 2.4 times more permeate flux than conventional thin film composite (TFC) membranes with the same chemical compositions and the same retention rate [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Their performance relies on their geometrical structure of pores, corresponding pore size distribution, and undesirable macrovoid formation across the entire film thickness. Usually, porous polymeric filtration membranes have their other intrinsic limitations, e.g., poor permeability, high operating pressures, limited available materials, cost effectiveness, and environmental concerns [8][9][10].…”
Section: Introductionmentioning
confidence: 99%